2017
DOI: 10.5194/acp-2016-1111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for renoxification in the tropical marine boundary layer

Abstract: <p><strong>Abstract.</strong> We present two years of NO<i><sub>x</i></sub> observations from the Cape Verde Atmospheric Observatory located in the tropical Atlantic boundary layer. We find NO<i><sub>x</i></sub> mixing ratios peak around solar noon (at 20–30 pptV depending on season), which is counter to box model simulations that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…x . An average EF of 10-30 is less than our upper limit of EF and would be within the range found by Reed et al 10 (EF = 10) and Kasibhatla et al 12 (EF = to best explain observations of HONO and NO x at the Cape Verde Observatory.…”
Section: Comparison Of Korus-aq To Other Measurementssupporting
confidence: 81%
See 1 more Smart Citation
“…x . An average EF of 10-30 is less than our upper limit of EF and would be within the range found by Reed et al 10 (EF = 10) and Kasibhatla et al 12 (EF = to best explain observations of HONO and NO x at the Cape Verde Observatory.…”
Section: Comparison Of Korus-aq To Other Measurementssupporting
confidence: 81%
“…[6][7][8] To reconcile models and observations, multiple pathways for the conversion of HNO 3 into NO x or HONO have been proposed, a process termed re-noxification. Various re-noxification pathways have been proposed in areas including the upper troposphere, [7][8][9] the marine boundary layer, 6,[10][11][12] rural forests, 13,14 and areas of continental outflow. 15 Recently, several of these studies have suggested that HNO 3 is rapidly photolyzed in aerosols to form NO 2 or HONO, at a rate between 10 and 300 times faster than the rate of gas-phase HNO 3 photolysis, [10][11][12]15,16 and it is this process that we investigate here.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary sources were thought to be dominated by homogeneous gas phase reaction of NO and OH during the day (resulting in a null cycle with R1), and heterogeneous production of HONO from NO2 on surfaces at night (Calvert et al, 1994;Finlayson-Pitts et al, 2003;Jenkin et al, 1988;Kleffmann et al, 1998;Stutz et al, 2002). More recently, studies have shown that heterogeneous reactions are also important sources of HONO during the day and include photo-enhanced reduction of NO2 on organic substrates (George et al, 2005;Monge et al, 2010;Stemmler et al, 2006) and nitrate photolysis (Reed et al, 2017;Ye et al, 2017;Zhou et al, 2011). Despite numerous studies over the last few decades, substantial uncertainties remain regarding the relative magnitude of these sources, with models frequently unable to account for total measured HONO concentrations without the inclusion of unknown sources, typically driven by photolysis (e.g.…”
Section: Introductionmentioning
confidence: 99%